Crystallographic characterization of fluorapatite glass-ceramics synthesized from industrial waste. (5th September 2017) - Loy, Chee W.; Matori, Khamirul A.; Zainuddin, Norhazlin; Whitten, Andrew E.; Rehm, Christine; de Campo, Liliana; Sokolova, Anna; Schmid, Siegbert
Abstract : A series of phase transformations of a novel fluoroaluminosilicate glass forming a range of fluorapatite glass-ceramics on sintering are reported. The sintering process induces formation of fluorapatite, mullite, and anorthite phases within the amorphous silicate matrices of the glass-ceramics. The fluoroaluminosilicate glass, SiO2 –Al2 O3 –P2 O5 –CaO–CaF2, is prepared from waste materials, such as rice husk ash, pacific oyster shells, and disposable aluminium cans. The thermally induced crystallographic and microstructure evolution of the fluoroaluminosilicate glass towards the fluorapatite glass-ceramics, with applications in dental and bone restoration, are investigated by powder X-ray diffraction and small-angle neutron-scattering techniques.